Basic Statistics 2017. (Metro Manila, Philippines Asian Development Bank, 2017)
Basic Statistics 2017 covers selected indicators of the Sustainable Development Goals (SDGs) such as the proportion of population living below 1.90 dollar(PPP) a day, maternal mortality ratio, carbon dioxide emissions, and proportion of individuals using the internet. It also contains data on basic social and economic indicators such as the population, gross domestic product (GDP), inflation rate, trade balance, external debt, fiscal balance, and others
Keywords: Statistics -- Economic aspects; Poverty; Sustainable development; Electronic books